Analisis Penyebab Cacat Kemasan pada Produk Abon Ayam di UMKM Matami Menggunakan Diagram Fishbone - Sakinah, Nur irni Nahri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, particularly in the processed food sector such as chicken floss products. However, packaging quality often becomes a major issue that lowers product competitiveness. This study aims to identify the types of packaging defects and analyze their root causes in the chicken floss product of UMKM MATAMI, located in Banggai Regency, Central Sulawesi. A qualitative descriptive approach was used with the fishbone diagram as the main analysis tool. Data were collected through observation, interviews, documentation, and literature studies. The findings reveal five dominant types of packaging defects, such as poorly sealed plastic and improperly attached labels. Fishbone analysis showed that the main causes stem from human factors, work methods, and machinery. The study recommends improvements including worker training, development of standard operating procedures (SOPs), machine maintenance, and simple quality control systems.